Artistic Means of Expressing Social Problems in the Poetry of E. Yevtushenko - M. K. Khusanboeva (Zien Journals, 2022)
This article examines the artistic means used to express social problems in the work of E.Yevtushenko. The purpose of the article is to study and describe the features of the verbal and artistic embodiment of the concept of «citizenship» in the works of E.A. Yevtushenko, to study the structure and verbal realizations of the concept of «citizenship» on the material of the works of E.A. Yevtushenko.
Keywords: linguistic picture of the world; lyrical hero; linguistic culture; national historical background